Pandangan Islam Mengenai Surat Kuasa Profesi Advokat dengan Al-Wakalah Ditinjau dari Ayat-Ayat Al-Qur’an dan Hadis - Denni Herdiansyah; Muhammad Royhan; Fauziah Lubis (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Indonesia as a state of law based on Pancasila and the constitution of the Republic of Indonesia year 1945, Indonesia is a country with a majority Muslim population, which makes Islam dominant in governing its people in every line of life It includes the teachings of truth, honesty, and justice that a person of law enforcement in Indonesia must possess. Advocate is one of the professions of law enforcement in Indonesia that have dedicated itself to the interests of the community and have contributed to the establishment of justice and truth. so the advocate profession has been called the “Officium Nobile" profession. In Islam, everything has been arranged in such a way that the welfare of Muslims is realized. This includes the matter of deputy representation in an affair (al-wakalah). n carrying out their duties as advocates, clients often represent themselves to advocates in litigating in court (legal Representation, due to matters that cannot be abandoned by the client or lack sufficient legal knowledge in litigation in court or because of the statutory requirements due to the threat of more than five years of confinement. So a power of attorney is issued that makes the basis for an advocate to have a case representing his client in court. In article 1792 KuhPer it is explained that a power of attorney is an agreement by which a person gives to another person who receives it on his behalf conducting an affair. The method used is normative juridical writing type, Research library data collection techniques (libraries) that emphasize sources of information from legal books, journals, papers, and opinions that have a relevant relationship to the problem under study. The result of this paper is a description of the harmony of the concept of power of attorney in Islam with a review of the verses of the Qur'an and Hadith. Keywords : Verses of the Qur'an, Hadith, Power of attorney, and al-Wakalah. Keywords: Verses of the Qur'an, Hadith, Power of attorney, and al-Wakalah.